Colonization of Citrobacter koseri and Streptococcus agalactiae in a case of cellulitis cruris dextra et sinistra - Luh Gede Melia Puspita Sari; Ni Nengah Dwi Fatmawati; I Gusti Ayu Agung Praharsini; Marvin Giantoro (Intisari Sains Medis, 2022)
Background: Cellulitis is a skin infection involving the deep dermis and subcutaneous tissue, characterized by localized pain, swelling, tenderness, erythema, and warmth. The most common causes of cellulitis are group A streptococci and Staphylococcus aureus. Streptococcus agalactiae or the so-called group B Streptococcus can also cause cellulitis. This case report aims to evaluate the colonization of Citrobacter koseri and Streptococcus agalactiae in a case of cellulitis cruris dextra et sinistra. Case Presentation: A 53-year-old married woman presented to the outpatient clinic complaining of swelling and redness in her left and right legs since five days ago. At first, there was only a little redness around the calf, but it became wider and pain in that area. On examination, there were multiple erythematous macules, patches, and multiple erosional lesions, warm palpable and tender to palpation, and the diascopy test disappeared with pressure. Based on the wound culture results, isolated Citrobacter koseri and Streptococcus agalactiae bacteria were considered colonization. Both of these bacteria were less virulent. The patient was treated with systemic and topical antibiotics, analgesics, wound care management and elevated lower limbs. Conclusion: The diagnosis of cellulitis is based on history and physical examination. On examination of the wound culture of this case, Citrobacter koseri and Streptococcus agalactiae were found, considered as colonization. The patient showed clinical improvement at each observation after administration of antibiotics and wound care management. The patient's prognosis is dubious ad bonam.